The Role of Concretions in Phosphorus Availability in a Typical Concretionary Soil of Northern Ghana - Abekoe, M.K. (University of Ghana, 1989)
Phosphorus deficiency is widespread in most soils of northern Ghana. Presence of lateritic concretions in some of the soils constitute an additional limitation to crop production in the region because the concretions act as an effective sink for added P. To assess the role of the concretions on phosphorus availability in a typical concretionary soil of northern Ghana, a soil originally containing 70% concretions was fractionated into soil fines and concretions and the soil reconstituted to represent varying amounts of the concretions. Phosphate sorption and desorption studies were carried out on samples containing 0%, 35%, 70%, 100% and a 2-mm sieved original soil. Phosphate sorption maximum varied among the test soils. The sample containing 0% concretion sorbed the least amount of P (110 μg/g) while increasing concretion content increased sorption with the highest sorption found with the 100% concretions (194 μg/g). Successive desorption of adsorbed phosphate using 0.01M KC1 indicated a lower percent P released by the sample containing 100% concretions (37% P released) than the soil fines, (67% P released) which desorbed the highest amount of P. However, the cumulative P desorbed after 8 successive extractions in both 0% and 100% concretions were similar, 117 μg/g and 103 μg/g respectively. This result suggests that both concretions and soil fines have an equivalent amount of labile P pool though the rate of P release is lower in the concretions than in the soil fines. The reversibility of P sorption in the concretions was also investigated in a greenhouse experiment. The test soils, (0%, 35%, 70% concretions and the original soil) were fertilized at two levels of P and were cropped with millet (Pennisetum typhoides). At the first cropping, both dry matter yield and total P uptake were highest in the sample containing 0% concretion at all levels of P applied. Total P uptake in the soil fines was 56.2 to 67.1 mg/pot, and that of the 70% concretions, 38.2 to 43.0 mg/pot. Subsequent croppings showed higher dry matter yield and P uptake in the concretionary soils but a sharp drop in the soil fines. This result is an indication of higher P release in the concretionary soils and an earlier exhaustion of P in the soil fines. At the end of the sixth cropping, the total quantities of P removed by the crop in the soil fines were 69,9 to 86.1 mg/pot, and in the test soil sample containing 70% concretions, 64.8 to 78.0 mg/pot. These results showed that differences in P released between soil fines and concretions had narrowed with successive croppings. In general the original soil behaved similarly to the 70% concretionary soil sample. Phosphate desorbed by the 0.01M KC1 extraction was found to be higher than plant P uptake but both followed the same trend. The results of both desorption studies and pot experiment suggest that the concretions do release part of the phosphorus sorbed but the major difference between the concretions and soil fines is the rate of P release.